THE DEVELOPMENT OF AUTHENTIC ASSESSMENT RUBRIC ON HISTORY OF ISLAMIC CULTURE SUBJECT AT ISLAMIC EDUCATION DEPARTMENT OF IAIN BATUSANGKAR - Romi Maimori (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
This research is motivated by the fact that there is no standardized rubric in assessing students’ performance either in performing the duties or in measuring the ability of students, especially for the subject of History of Islamic Culture taught to the students of Islamic Religious Education at IAIN Batusangkar. This research is a development research using Instructional Development Institute (IDI) model. The development procedure starts from planning, in the form of preliminary research and information gathering, until expert validation and product practice test. In the stage of expert validation, there are three aspects reviewed in the rubric developed, such as the material, construction and language aspects. Then, based on the three experts’ validation results, it is shown that this authentic scoring rubric has very valid criteria on material aspects with an average of 3.57. In aspects of construction rubric authentic assessment also has a very valid criteria with an average of 3.67 while the language aspect obtained an average of 3.23 with the category is very valid. Hence, overall an authentic scoring rubric developed based on expert validation results has a very valid criterion with an average value of 3.53, whereas the authentic assessment rubric practicality analysis is known that this rubric is very practical to use, with a practicality value of 890.63 and an average practical value of 89.06 with a very practical category.